Measures of preventing pneumonia associated with mechanical ventilation. (Salud, Arte y Cuidado, 2018)
Establish an adequate diagnosis of mechanical ventilation-associated pneumonia is one of the requirements most important and difficult in the care of patients in critical condition. The objective of this study was to evaluate the implementation of prevention measures of mechanical ventilation-associated pneumonia. Intensive care unit nursing staff. This research is located in the paradigm quantitative, positivist, non-experimental, descriptive supported with field design, cross. The population was 6 patients who nurses was low and care observation technique, is used as a tool for data collection; a list of matching, the implementation of measures for the prevention of pneumonia associated with mechanical ventilation through a list of statements to determine if it does or does not, i.e., with response dichotomous was recorded. The instrument consisting of 46 statements distributed in 4 dimensions. We conclude a large percentage complies with the application of the technique of hand-washing and runs properly the movement of patients so that they are more comfortable and his recovery is satisfactory, likewise, care pre intra and post aspiration of subglottic secretions and the oral cavity disinfection, a high percentage compliance with precautions and care in all phases, while in the changes of the circuits of the fan and the use of humidifiers pre vacuum circuits all comply with care.
Keywords: pneumonia; mechanical ventilation; prevention; nursing